Genetic characterisation of staphylococci of food-producing animals in Senegal. PVL detection among MSSA - Mama, Olouwafemi Mistourath (BMC Vet Res, 2019)
BACKGROUND: Food-producing animals can be a vehicle for staphylococcal species as well as their virulence and antimicrobial resistance genes. This work aimed to analyse the diversity of staphylococcal species in food-producing animals in Dakar/Senegal, and to determine the antimicrobial resistance phenotype/genotype and virulence factors of recovered isolates. Nasal samples of 149 cows and 199 chickens (348 animals) were collected from one slaughterhouse and a local market respectively, and were inoculated on selective media for staphylococci recovery. For S. aureus isolates, molecular typing (spa-type, MLST) was performed by PCR/sequencing, and the presence of 27 virulence genes (exfoliative and toxic shock toxins, PVL, haemolysins and enterotoxins) as well as the gene scn were analysed by PCR. Susceptibility to twelve antibiotics was studied by disc-diffusion method for all staphylococci; the resistance genes involved were screened by PCR. RESULTS: Staphylococcus spp. was present in 3 and 26.8% of chicken and cow nasal samples, respectively. Seven S. aureus isolates and forty isolates of other staphylococcal species were identified. S. aureus isolates were recovered from cow (n = 6) and chicken (n = 1) samples, belonging to four genetic lineages: t084/ST15 (n = 1); t10579/ST291 (n = 3); t355, t4690/ST152 (n = 2); and t6618/ST6 (n = 1). All S. aureus were methicillin-susceptible, penicillin-resistant (blaZ), and two of them were also tetracycline-resistant [tet(K)]. All the isolates carried at least one of the virulence genes tested. The PVL genes were detected in three ST15 and ST152 isolates. They all harboured haemolysins encoding genes and lacked the scn gene. The other staphylococci recovered were S. sciuri (n = 16), S. simulans (n = 11), S. hyicus (n = 5), S. haemolyticus (n = 4), S. chromogenes (n = 3), and S. hominis (n = 1); they were all methicillin-susceptible and 27.5% tetracycline-resistant [tet(K) and tet(L)]. CONCLUSIONS: A low prevalence of S. aureus was detected among food-producing animals, all susceptible to methicillin. However, the presence of virulence genes (lukF/lukS-PV, eta, tst, sea and see) is worrisome to the extent that they could be transferred to derived food and therefore, to humans.